Finding Scotland's Cinema Factor: From The Cinema in Education (1925) to The Film in the Classroom (1933). Issue 3 (2nd September 2019) - Bohlmann, Julia
Abstract : This article discusses two experiments that aimed to establish the educational value of cinema: the 1925 Cinema Commission's report The Cinema in The Author(s)Education, and The Film in the Classroom, an experiment carried out by Glasgow Corporation between 1932 and 1933. Both experiments were part of a discourse on educational cinema that recognized film as a powerful visual medium with a profound impact on how children learned about and interacted with the world around them. The experiments contributed to the fledging of the educational film movement of the 1930s without, however, mirroring the transition to sound occurring in cinemas at that time.